Experiences with remote communication in adult intensive care units during the COVID-19 pandemic: A systematic review protocol. - Fernandes, António Manuel Martins Lopes (2023)
Objective: The objective of this review is to explore the lived experiences of critically ill adults, their families, or health care professionals with remote communication in intensive care units (ICUs) during the COVID-19 pandemic. Introduction: Family visiting restrictions in ICUs during the COVID-19 pandemic imposed significant challenges to communication between critically ill adults, their families, and the health care team. Evidence shows that several communication strategies were developed and implemented in ICUs during the COVID-19 pandemic to promote family engagement; however, the experiences of critically ill adults, their families, and health care professionals with these strategies are scattered across primary qualitative studies. Inclusion criteria: This review will consider qualitative studies that include critically ill adults, their families, or health care professionals, focusing on their experiences with remote communication strategies in ICUs during the COVID-19 pandemic. Methods: This review will be conducted in accordance with JBI methodology. The search strategy will aim to locate both published and unpublished qualitative studies in English, Spanish, and Portuguese. Studies published after January 2020 will be included. Study selection, critical appraisal, and data extraction will be performed independently by 2 reviewers. Data will be presented in narrative format and synthesized using the JBI meta-aggregation process. A ConQual Summary of Findings will be presented.